2006
DOI: 10.1369/jhc.6a6927.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Enzymes Involved in Estrogen Metabolism in Human Prostate

Abstract: There is evidence that estrogens can directly modulate human prostate cell activity. It has also been shown that cultured human prostate cancer LNCaP can synthesize the active estrogen estradiol (E2). To elucidate the metabolism of estrogens in the human prostate, we have studied the expression of enzymes involved in the formation and inactivation of estrogens at the cellular level. 17beta-Hydroxysteroid dehydrogenase (17beta-HSD) types 1, 2, 4, 7, and 12, as well as aromatase mRNA and protein expressions, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 53 publications
1
25
0
3
Order By: Relevance
“…Furthermore, estrogenmetabolizing enzymes such as aromatase, sulfatase, sulfotransferase, and 17b-hydroxysteroid dehydrogenases (17b-HSDs) exist in stromal cells adjacent to the tumor. These convert androgens and inactive estrogens (estrone (E1), estrone sulfate) into active estrogen (17b-estradiol, E 2 ; Pasqualini & Chetrite 2006, Takase et al 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, estrogenmetabolizing enzymes such as aromatase, sulfatase, sulfotransferase, and 17b-hydroxysteroid dehydrogenases (17b-HSDs) exist in stromal cells adjacent to the tumor. These convert androgens and inactive estrogens (estrone (E1), estrone sulfate) into active estrogen (17b-estradiol, E 2 ; Pasqualini & Chetrite 2006, Takase et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatase is a key enzyme that catalyses the conversion of androgens to estrogen (Pasqualini & Chetrite 2006, Takase et al 2006. Aromatase mRNA is expressed in various tissues, such as adipose tissue, bone, brain, skin, and breast cancer (Bulun et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue aromatase levels in both epithelium and stroma were associated with longer time to biochemical recurrence or disease progression (Grindstad et al 2016). Increased expression of aromatase has been reported in periprostatic adipose tissue, PCa cells and particularly metastatic CRPC (Hiramatsu et al 1997, Ellem et al 2004, Takase et al 2006, Montgomery et al 2008, Celhay et al 2010. Prior clinical trials of aromatase inhibitors in PCa patients showed no benefit (Santen et al 2001, Smith et al 2002.…”
Section: Estrogen and Progesteronementioning
confidence: 99%
“…The prostate likewise possesses all the necessary enzymes to convert circulating DHEA into estradiol and testosterone, as well as 5a-reductase to convert testosterone to the more bioactive dihydrotestosterone (Takase et al, 2006).…”
Section: Formation and Transformation Of Tissue Estrogen Levels In Thmentioning
confidence: 99%